Policy Trade Balance Formed from Indonesian Plastic Industry Exports - Ratnasih, Cicih; Saleh, Sugiyanto; Damayanti, Dian (Dinasti Publisher, 2025)
This research investigates how Indonesia’s plastic product exports influence the national trade balance, drawing comparative lessons from fellow ASEAN economies. Employing a multiple linear regression approach, the study evaluates the impact of five macroeconomic indicators—exchange rate, foreign direct investment (FDI), inflation, production volume, and logistics infrastructure—on export performance. The analysis reveals that all variables exert statistically significant effects, with FDI inflows and infrastructure quality emerging as the most influential drivers of export growth. A weaker exchange rate tends to bolster export competitiveness, whereas inflation undermines cost-efficiency and market viability. Higher production output and enhanced logistics systems contribute directly to increased export capacity and operational effectiveness. The findings underscore the need for integrated macroeconomic strategies focused on inflation control, investment attraction, and infrastructure development to reinforce Indonesia’s trade balance through plastic industry exports. These policy directions align with ASEAN’s broader agenda for industrial resilience and export-oriented development.